Ras gene mutations in vinyl chloride‐induced liver tumours are carcinogen‐specific but vary with cell type and species - Boivin-Angèle, Sandra; Wegener, Kurt; Bartsch, Helmut (International journal of cancer, 2000)
Previous studies have shown that a high proportion (5/6) of human liver angiosarcomas (ASL) associated with exposure to vinyl chloride (VC) contains a GC→AT mutation at the Ki‐ras codon 13. This mutation, however, has not been found in 5 ASL or 2 hepatocellular carcinomas (HCC) induced in rats by VC.
Gesehen am 02.02.2021